Flow diverter treatment of intracranial vertebral artery dissecting pseudoaneurysms. (24th April 2017) - Cerejo, Russell; Bain, Mark; Moore, Nina; Hardman, Julian; Bauer, Andrew; Hussain, M Shazam; Masaryk, Thomas; Rasmussen, Peter; Toth, Gabor
Abstract : Introduction: Intracranial vertebral dissecting pseudoaneurysms are a rare, but increasingly recognized, cause of subarachnoid hemorrhage and ischemic stroke. The risks of aneurysm re-rupture and associated morbidity are high. The use of flow diverter stents for the treatment of these aneurysms has not been well studied. Objective: To report our data and provide a summarized review of literature using flow diverter stents for the treatment of intracranial vertebral artery dissecting pseudoaneurysms. Methods: We performed a retrospective analysis of flow diverter stents used for the treatment of intracranial vertebral artery dissecting pseudoaneurysms. Clinical, imaging, procedural, and follow-up data were collected. Results: We identified eight vertebral dissecting pseudoaneurysms in seven patients (5 (71.4%) female; median age 47 years (IQR 46–52)) who had undergone treatment with flow diverter stents. In 4/7 patients (57.1%) the aneurysm had ruptured; however, only one was treated in the acute phase. Median size of the largest diameter of the aneurysm was 6.3 mm (IQR 4.2–8.8), and 7/8 aneurysms (87.5%) were treated with a single flow diverter device. Three aneurysms were concurrently coiled. Angiographic complete occlusion was seen in 6/8 (75%) aneurysms at a median follow-up of 14 months (IQR 7.7–20.2). Two patients had periprocedural strokes with transient neurologic deficits. All patients had a good clinical outcome (modified Rankin Scale score ≤2). There were no re-treatments or aneurysm ruptures during the follow-up period. Conclusions: Our experience suggests that flow diverter stent treatment of intracranial vertebral artery dissecting pseudoaneurysms is safe, and associated with good occlusion rates and favorable clinical outcomes.